Jurisprudence of narrations of Om Al-Fadhl (Lubna Bint Al-Harith) - Ali, Ghassan Selman (Al-Adab Journal, 2018)
As an example of kindness Allah granted our prophet great companions and great wives, they were trustee in informing us all his narrations I have chosen (Om Al-Fadhl )because she was very close to our prophet ,she was sister of (Maymonah Bint Al-Harith ) and wife of (Al-Abbas Bin Abdul Mutalib ) uncle of our prophet In addition to her being close to our prophet she had very much knowledge about prophetic Hadith Requirements of this research were preface, seven themes, and an end Preface contains a brief biography of Om Al-Fadhl First theme :Rule of urine of boys. Second theme : Rule of prayer in one dress Third theme : Rule of fasting day of Arafa for pilgrim Forth theme : Rule of fasting days of (Tashreeq Fifth theme : Rule of Number of forbidden breastfeeding Sixth theme :Rule of marriage of young girls Seventh theme : Invocation of God to keep well a person who sneezes. An end of this research was the important results of this research In the end I wish that others can make use of my research.